A Financial Conditions Index for South Africa - Gumata, Nombulelo (IMF Working Papers; Working Paper ;, 2012)
The main purpose of this paper is to construct a financial conditions index (FCI) for South Africa. The analysis extracts the index by applying two alternative approaches (principal component analysis and Kalman filter), which identify an unobservable common factor from a group of external and domestic financial indicators. The alternative estimated FCIs, which share a similar trajectory over time, seem to have a powerful predictive information for the near-term GDP growth (up to four quarters), and they outperform the South African Reserve Bank's (SARB) leading indicator as well as individual financial variables. Their recent dynamics suggest that following a strong recovery in late-2009 and 2010, reflecting in part domestic factors such as systematic reductions in the policy rate, the rebound in real economic activity, and a benign inflationary environment, the financial conditions have deteriorated in recent months, though not as sharply as in end-2008. Given their relatively high predictive power regarding GDP growth, a further deterioration may imply that economic activity is likely to slow in the period ahead.